Effect of acupuncture on ischaemic stroke in patients with rheumatoid arthritis: a nationwide propensity score-matched study - Cheng-Li Lin; Chia-Yu Huang; Ming-Cheng Huang; Hou-Hsun Liao; Yu-Chen Lee; Gregory Zimmerman; Mei-Yao Wu; Hung-Rong Yen (BMJ Open)
Objective To demonstrate that acupuncture is beneficial for decreasing the risk of ischaemic stroke in patients with rheumatoid arthritis (RA).Design A propensity score-matched cohort study.Setting A nationwide population-based study.Participants Patients with RA diagnosed between 1 January 1997 and 31 December 2010, through the National Health Insurance Research Database in Taiwan.Interventions Patients who were administered acupuncture therapy from the initial date of RA diagnosis to 31 December 2010 were included in the acupuncture cohort. Patients who did not receive acupuncture treatment during the same time interval constituted the no-acupuncture cohort.Primary outcome measures A Cox regression model was used to adjust for age, sex, comorbidities, and types of drugs used. We compared the subhazard ratios (SHRs) of ischaemic stroke between these two cohorts through competing-risks regression models.Results After 1:1 propensity score matching, a total of 23 226 patients with newly diagnosed RA were equally subgrouped into acupuncture cohort or no-acupuncture cohort according to their use of acupuncture. The basic characteristics of these patients were similar. A lower cumulative incidence of ischaemic stroke was found in the acupuncture cohort (log-rank test, p<0.001; immortal time (period from initial diagnosis of RA to index date) 1065 days; mean number of acupuncture visits 9.83. In the end, 341 patients in the acupuncture cohort (5.95 per 1000 person-years) and 605 patients in the no-acupuncture cohort (12.4 per 1000 person-years) experienced ischaemic stroke (adjusted SHR 0.57, 95% CI 0.50 to 0.65). The advantage of lowering ischaemic stroke incidence through acupuncture therapy in RA patients was independent of sex, age, types of drugs used, and comorbidities.Conclusions This study showed the beneficial effect of acupuncture in reducing the incidence of ischaemic stroke in patients with RA.